2022
DOI: 10.1080/08897077.2021.1975871
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phone and Internet use among People who Inject Drugs: Implications for Mobile Health Interventions

Abstract: Background: Mobile health (mHealth) interventions have the potential to improve substance use treatment engagement and outcomes, and to reduce risk behaviors among people who inject drugs (PWID). However, there are few studies assessing mobile technology use among PWID and none have investigated continuity of mobile phone use. Methods: We surveyed 494 PWID. We used bivariate (independent-sample t- and chi-square tests) and multivariate (logistic regression) analyses to determine whether mobile phone and/or int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…This is similar to findings of the study among youth whereby 48% had smartphones ( 37 ) and high mobile phone penetration in the general population ( 21 , 23 ). This is also consistent with other studies where phone ownership among individuals with OUD ranges between 77%–89% ( 28 , 33 , 34 ). Access to other digital technologies was lower with 25% and 30% reporting access to computer and internet respectively.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is similar to findings of the study among youth whereby 48% had smartphones ( 37 ) and high mobile phone penetration in the general population ( 21 , 23 ). This is also consistent with other studies where phone ownership among individuals with OUD ranges between 77%–89% ( 28 , 33 , 34 ). Access to other digital technologies was lower with 25% and 30% reporting access to computer and internet respectively.…”
Section: Discussionsupporting
confidence: 93%
“…There was a high phone turnover with 57.2% reporting to have changed phone at least once in past year mainly due to phones getting lost and stolen which is a pattern common in individuals with SUD ( 28 , 31 , 33 , 34 ). This implies a potential challenge when assessing the effectiveness of an intervention over a follow up period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This community-academic partnership is a strong example of developing harm reduction-oriented digital platforms that prioritizes Further, creating overdose data collection tools designed for people who use drugs that provide an added benefit or incentive for reporting may be another effective pathway to improve data. A recent study found that approximately 77% of people who inject drugs have a mobile phone and of those with a mobile phone, 88% have a smart phone with voice and internet service [25]. Future studies should incorporate people who use drugs in a co-design process to solve this problem and develop a solution that preserves trust, protects the population, and improves overdose data.…”
Section: Discussionmentioning
confidence: 99%
“…Working cell phone access is known to be low in some groups who use drugs (Ozga et al 2022), but has not been explored with LSD use, so this variable was added. Finally, since parenthood is associated with decreased substance use (Fergusson, Boden, and John Horwood 2012), but also has not been investigated with LSD use, variables on the number of children under 18 years of age in the home and current pregnancy were incorporated into the models.…”
Section: Tables / Figuresmentioning
confidence: 99%